1977
DOI: 10.1002/1097-0142(197701)39:1<1::aid-cncr2820390102>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Combination chemotherapy with bis chloroethyl nitrosourea (BCNU), vincristine and dimethyl triazeno imidazole carboxamide (DTIC) in disseminated malignant melanoma

Abstract: One hundred thirty two patients with disseminated malignant melanoma were treated using a combination of BCNU, vincristine and imidazole carboxamide. A response rate of 23% was observed, while 16% had stable disease. The patients' median survival was 42 months from diagnosis and 5.3 months from the onset of treatment. These results are not significantly different from therapy with imidazole carboxamide alone. Patients on this study were observed to have a significant reduction in the number of lymphocytes in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 10 publications
1
9
0
Order By: Relevance
“…119 This is similar to the appearance of phagocytic signet ring cells observed in secondary metastatic lesions in other breast cancer patients. 123 Additionally, the number of phagocytic tumor cells present within the tumor stroma correlates with breast cancer malignancy and grade.…”
Section: Macrophages and Metastasissupporting
confidence: 79%
“…119 This is similar to the appearance of phagocytic signet ring cells observed in secondary metastatic lesions in other breast cancer patients. 123 Additionally, the number of phagocytic tumor cells present within the tumor stroma correlates with breast cancer malignancy and grade.…”
Section: Macrophages and Metastasissupporting
confidence: 79%
“…The 300 response rate for DTIC + AMSA, although inferior to results of other such combinations as DTIC + BCNU + Vinca alkaloids [7] with a 40~ response rate or Cisplatin + Bleomycin + Vinblastine with a 38~ response rate [9,10] is superior to the 20-25070 response rate of DTIC alone [5]. The toxicity of the AMSA + DTIC combination, even when both drugs were used at full dosage was not serious, probably because of the different spectrum of their toxicity.…”
Section: Discussionmentioning
confidence: 86%
“…The toxicity of the AMSA + DTIC combination, even when both drugs were used at full dosage was not serious, probably because of the different spectrum of their toxicity. We conclude that, although AMSA alone has minimal activity in melanoma, it seems to enhance the activity of DTIC without significant toxicity compared with DTIC combinations with more myelotoxic drugs [7,9,10].…”
Section: Discussionmentioning
confidence: 99%
“…In just such an extended study by Cohen et al again, a response rate of but 43% was found . In three other studies of the same combination of agents in lower dosages, or comparable dosage, but with hydroxyurea instead of vincristine, response rates of 23%, 15–27%, and 33%, respectively were obtained. The study of Hill et al showed response rates to the combination that were not different from those to DTIC alone.…”
Section: Combination Chemotherapymentioning
confidence: 89%
“…It will be important now to confirm the study of this combination. With these notable exceptions, all trials to date of combination chemotherapy for malignant melanomas are reported to show favorable responses in less than 30% of patients treated and suggest that these combinations are no better than single‐agent therapy with DTIC ,,,,,,,,,. It must be concluded that there is as yet no convincing advantage of combination chemotherapy over single agents for malignant melanoma, and that combination drug therapy should still be undertaken as investigational.…”
Section: Combination Chemotherapymentioning
confidence: 99%